Leadership in school management, brief analysis (Research, Society and Development, 2022)
Faced with the advancement of technologies, the globalization process and the social transformations as a result of these, Education and educational management needed to evolve into the practice of democracy, bringing new concepts such as democratic management and leadership as well as contextualized meanings. The present study is justified because it is necessary to highlight the leadership of the school manager in order to briefly analyze its developments in the context of school organization, working on concepts and meanings. To carry out this study, qualitative research was used, in relation to the objective, it is an exploratory and descriptive research and on the research procedures, the study was characterized as bibliographic. The research was carried out in a virtual environment, in reliable databases such as Scielo, published scientific, books and complete original works, with the descriptors: education, management and leadership. The results and discussions are exposed in two titles, namely: School management and Leadership in School Management and its importance. The conclusions were expressed right after the results and discussions as well as the author's impressions.